Foreign firms in Portuguese manufacturing and retail sectors: a similar or different location - J. Cadima Ribeiro; J. Freitas Santos (European Regional Science Association (ERSA), 2001)
Foreign Directo Investment (FDI) is increasingly important in the portuguese economy since it integration in the European Union (1986), although from 1997 onwards it has considerably decreased. In 1995 and 1996, the share of the FDI in the GDP reached it peak obtaining a value of 4,29 and 4,34 respectively. The manufacturing and retailing sectors represent a good part of the total FDI. In this paper we investigate the industrial and retail services location factors. Two surveys have been carried out allowing for the identification of the most preferable factors by the foreign investors. In the manufacturing sector the selection of Portugal to invest depended upon the labour costs and the importance of domestic market. In the retailing sector the government regulations, market size, cultural and geographic proximity to the host country are the most relevent factors.
Keywords: 330